IMPACT OF CRUDE OIL POLLUTION ON SOIL THERMAL PROPERTIES (THERMAL CONDUCTIVITY, THERMAL DIFFUSIVITY AND THERMAL RESISTIVITY) IN OGONILAND RIVERS STATE SOUTH-SOUTH NIGERIA - Maina, Mohammed; Likkason, Othniel Kamfani; Ali, Sani; Samaila, Nuhu K. (FUDMA JOURNAL OF SCIENCES, 2025)
Soil thermal properties are required in many areas of engineering, agronomy, and soil science, and in recent years considerable effort has gone into developing techniques to determine these properties. Seed germination, seedling emergence, and subsequent stand establishment are influenced by the microclimate. Thermal properties of soils play an important role in influencing microclimate. In this study, the effect of soil thermal properties were assessed based on thermal conductivity, thermal diffusivity and thermal resistivity of soil samples polluted by crude oil and its spillage in Ogoniland Rivers State South-South Nigeria.  Soil samples at different test points (locations) were collected at depths of 0 – 15 cm for topsoil and 15 – 30 cm for subsoil with the aid of Dutch stainless steel hand auger from four (4) sites (impacted) within the study area and one (non-impacted) control site (outside) the study area. Thermal properties (diffusivity, conductivity and resistivity) were determined and the soils at these specified depths and their values were compared to those outside the study areas (control sites). The results show that there are negligible effects of crude oil pollution on soil thermal properties in both impact site and non-impact site at different test points. The soils in Eleme, Gokana and Tai Local Government Areas were found to be fitted for agricultural activities, laying of gas pipeline and buried of cable for telecommunication industries. The thermal properties of the soil are within the values previously reported by previous researchers.